The amygdala-insula-medial prefrontal cortex-lateral prefrontal cortex pathway and its disorders - Dorit Ben Shalom (Frontiers Media S.A., 2022)
Smith and Lane have suggested a model of emotion processing with at least three stations: areas like the amygdala, which process discrete body features areas like the anterior insula, which process whole-body patterns and areas like the medial prefrontal cortex, which process emotion concepts. Ben Shalom and Bonneh have suggested a model of the prefrontal cortex, in which medial BA 9 integrates emotional states, and lateral BA 9 performs selection/inhibition on these states. Taken together, the current paper suggests a pathway for emotion processing with at least four stations: areas like the amygdala, which process discrete body features areas like the anterior insula, which process whole-body patterns, medial BA 9 which integrates emotion concepts, and lateral BA 9, which performs selection/inhibition on these concepts. Following the existing literature, it then suggest that there is a significant involvement of the amygdala in psychopathy (Blair), of the anterior insula in alexithymia (Bird), of the medial BA 9 in deficits in somatosensory discrimination (Ben Shalom), and of lateral BA 9 in emotional impulsivity (Ronel).